Thermal and dielectric properties of ferroelectric lead germanate single crystals doped with chromium ions (Pb5Ge3O11:Cr3+). (3rd October 2018) - Bachulska, U.; Jankowska-Sumara, J.; Majchrowski, A.; Chrunik, M.; Zasada, D.; Soszyński, A.
ABSTRACT: Single crystals of Pb5 Ge3 O11 (PGO), pure and doped with Cr 3+ ions, were grown by means of Czochralski and Kyropoulos method, respectively. Structural, microstructural, thermodynamic and dielectric properties were investigated in terms of Cr 3+ -doping. The temperature dependences of molar heat capacity in the range 120–700 K at constant pressure ( cp ) for PGO and PGO:Cr 3+ (0.2%) crystals were shown. Wide λ-shape anomalies correspond to the second-order phase transitions from ferroelectric to the paraelectric phase taking place at 453 K and 431 K for PGO and PGO:Cr 3+ (0.2%), respectively. The temperature dependences of cp for investigated crystals were approximated by the Einstein function and near the Curie temperature the cp reaches the classical Dulong-Petit limited value ∼475 J·mol −1 ·K −1 . Temperature dependences of dielectric permittivity measured along and perpendicular to the ferroelectric axis in the temperature range 300–550 K are investigated. These studies revealed anisotropic behavior of PGO and PGO:Cr 3+ (0.2%) crystals.